Sartre et Foucault : l’hétérotopie du jardin public dans La Nausée (ENTHYMEMA, 2020)
The heterotopia is a concept forged for the first time by Michel Foucault and it is a physical localization of the utopia, linked to two other concepts: the heterology and the heterochrony. The heterology is a discourse about the “other”, while the heterochrony is a kind of temporal utopia. Literature offers innumerable examples of heterotopias which give the possibility to meditate about the idea of “otherness”. This article shows that the foucauldian concept of heterotopia can be applied to La Nausée by Sartre, and focuses on a particular heterotopia that is present in Sartre’s work: the public garden.
Keywords: Jean-Paul Sartre; Michel Foucault; literature; philosophy; heterotopy; heterology; heterochrony